A Study of Service Quality and Customer Satisfaction in Banks at Kaithal: An investigation into the perception of service quality and customer satisfaction in the banking industry at Kaithal, India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In India, banking industry is growing at a very fast rate. It can be said that it is growing exponentially. A number of studies are conducted covering various aspects of banking. As a regular customer of banks I was keen to know that whether the customers in the banking industry are satisfied with the service provided by the banks or not. My study is based on how the customers perceive the services of banks. . The objective of the study is to study the perception of respondents towards service quality and customer satisfaction in banks. For achieving the objective of the study primary data has been collected through questionnaire.